Hubungan Umur Ibu, Riwayat Abortus dan Jarak Kehamilan Terhadap Kejadian Abortus Imminens di Rumah Sakit Muhammadiyah Palembang tahun 2022 - Haliyati, Ica; Ciselia, Dewi; Afrika, Eka (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The Maternal Mortality Rate (MMR) is one of the global Sustainable Development Goals (SDGs) targets in reducing the maternal mortality rate (AKI) to 70 per 100,000 live births by 2030. One of the causes of bleeding in the first and second trimesters of pregnancy is abortion. Several factors predispose to abortion, for example fetal factors, maternal factors, environmental factors, age, parity, occupation and history of abortion. The purpose of this study was to determine the relationship between maternal age, history of abortion and gestational spacing simultaneously with the incidence of imminent abortion at Palembang Muhammadiyah Hospital in 2022. The study design used an analytical survey with a cross sectional approach. The population in this study were all inpatient pregnant women who were recorded in the register book at the midwifery room at the Muhammadiyah Hospital in 2022, a total of 1150 pregnant women. The sampling technique in this study was carried out by systematic random sampling with a total sample of 92 respondents. Data collection uses a checklist sheet. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study showed that there was a relationship between maternal age (p value = 0.038), history of abortion (p value = 0.005) and the distance between pregnancies (p value = 0.015) with the incidence of imminent abortion at Muhammadiyah Palembang Hospital in 2022. It is hoped that the results of this study can be an illustration for the hospital to be able to further improve health services, especially dealing with cases of imminent abortion.